Implementation of effective communication in nursing: A literature review - Nur Sriyanti; Lisa Musharyanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Effective communication has an important role in patient safety management, namely minimizing and preventing actions that are detrimental to nursing care. Implementation of effective communication requires various methods to maximize message delivery in order to realize patient safety and reduce work risks for nurses and other health workers. this can be started by taking into account the Standard Operating Procedures for implementing effective communication to the use of virtual technology. Identifying the implementation of effective communication in the context of patient safety in nursing care settings is the aim of this study. The article search method is by searching for journal articles through 2 databases namely Scopus and Pubmed. The method of analysis is done by selecting journals according to the purpose of writing and then reading one by one the journals that have been collected. For inclusion criteria in the preparation of this literature review are communication, health professionals, health student, nursing service setting, and journal articles for the last 5 years. The exclusion criteria; not open access journals, unclear or unstructured research methods, articles only in abstract form, non-systemic review and scoping review. Results: Through the feasibility test, 10 journal articles were obtained showing the implementation of effective communication in the context of patient safety and some of them were PBP simulation programs in the E-Learning module, TeamSTEPPS training, LEAN management, and virtual technology for navigating the treatment room. Effective communication can be carried out properly and directed if nurses are able to choose effective communication methods in nursing service settings according to field situations Abstrak: Komunikasi yang efektif memiliki peran penting dalam manajemen keselamatan pasien yaitu meminimalkan dan mencegah tindakan yang merugikan asuhan keperawatan. Pelaksanaan komunikasi yang efektif memerlukan berbagai metode untuk memaksimalkan penyampaian pesan guna mewujudkan keselamatan pasien dan mengurangi risiko kerja bagi perawat dan tenaga kesehatan lainnya. Hal ini dapat dimulai dengan memperhatikan Standar Operasional Prosedur (SPO) untuk melaksanakan komunikasi yang efektif dengan penggunaan teknologi virtual. Tujuan penelitian ini adalah untuk mengidentifikasi implementasi komunikasi efektif dalam konteks keselamatan pasien di setting asuhan keperawatan. Metode pencarian artikel adalah dengan mencari artikel jurnal melalui 2 database yaitu scopus dan Pubmed. Metode analisis dilakukan dengan memilih jurnal sesuai dengan tujuan penulisan kemudian membaca satu persatu jurnal tersebut yang telah dikumpulkan. Untuk kriteria inklusi dalam penyusunan literature review ini adalah komunikasi, tenaga kesehatan, mahasiswa kesehatan, setting pelayanan keperawatan, dan artikel jurnal selama 5 tahun terakhir. Kriteria eksklusi; tidak membuka jurnal akses, metode penelitian yang tidak jelas atau tidak terstruktur, artikel hanya dalam bentuk abstrak, review non sistemik dan scoping review. Hasil: Melalui uji kelayakan, diperoleh 10 artikel jurnal yang menunjukkan implementasi komunikasi efektif dalam konteks keselamatan pasien dan beberapa di antaranya adalah program simulasi PBP dalam modul E-Learning, pelatihan TeamSTEPPS, manajemen LEAN, teknologi virtual untuk navigasi ruang perawatan. Komunikasi yang efektif dapat terlaksana dengan baik dan terarah apabila perawat mampu memilih metode komunikasi yang efektif dalam setting pelayanan keperawatan sesuai dengan situasi lapangan.